An Assessment of Text Reading Habits of Pakistani M.Phil. Level Students - Sajid, Muhammad Khalid Mehmood; Hafizoah, Kassim; Al Fraidan, Abdullah; Hasan, Ghassan Adnan; Iqbal, Zafar; Aljarrah, Khaled; Al Anazi, Nawaf (PalArch Foundation, 2020)
Reading can play a vital role in personality development. No one can neglect its importance. But recent trendsshow that students’ priorities are changing overtime, and they are interested more in social media, entertainment, and reading novels. The purpose of reading is specific to them. Reading can make students optimistic and ambitious about their dreams.It is crucial to learn the easy and effective ways of reading at the university level because university level study is different from school and college level.University M.Phil. level requiresvariousforms and patternsof reading to achieve excellent grades. This study attempts to analyze the reading habit of students at a leading public university in Multan city. The purpose of the study is to measure the reading habits of M.Phil.Level students by percentage in the Economics department. It is a case study in which a questionnaire wasapplied to collect data from the Economics Department of Bahauddin Zakariya University Multan, Pakistan. A sample size of 30 respondentsat M.Phil. level was used to collect the data from the Economics Department of the University.The findings of the study showedpoor reading habitsamong the students while their interest was high towards social media, using the internet, and other activities. They like to read novels and other reading stuff instead of reading course books.